Computational study of spout collapse and impact of partition plate in a double slot‐rectangular spouted bed. Issue 12 (4th August 2015) - Yang, Shiliang; Zhang, Ke; Chew, Jia Wei
Abstract : Gas‐solid hydrodynamics in a three‐dimensional slot‐rectangular double‐spouted bed was numerically investigated by a combined approach of discrete element method and computational fluid dynamics, and the knowledge gained was extended to understand the mechanisms leading to operational instability due to the collapse of a spout, along with the beneficial impact of inserting a vertical partition plate. The setup investigated has two diverging bases and contains up to 2, 590, 000 particles. The computational results show different behaviors of pressure drop, in terms of average value, fluctuations, and power spectral trends, in the five distinct flow regimes corresponding to various superficial gas velocities. Two types of spout shapes are observed under stable spouting conditions, and the spout sizes are quantified. When one of the spouts chokes then collapses, complex interactions between the chambers are identified. Furthermore, the insertion of a vertical partition plate between two chambers appears to be an effective way to prevent the interactions between adjacent fountains, which is advantageous for improving the operational stability of such systems upon scale‐up. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4087–4101, 2015